Associations of depressive symptoms, social engagement and support, and lifestyle behaviors among non-Hispanic black and Hispanic men with chronic conditions in the United States - Park, Jeong-Hui; Bergeron, Caroline D.; Ness, Michael; Sherman, Ledric D.; Merianos, Ashley L.; Yoo-Jeong, Moka; Cisneros Franco, Cynthia L.; Tomar, Aditi; Boolani, Ali; Kew, Chung Lin; Oloruntoba, Oluyomi; Smith, Matthew Lee (Frontiers in Public Health, 2025)
IntroductionSelf-management of depressive symptoms is influenced by co-morbidity, social support, and health-related behaviors. Men are less likely to discuss depressive moods and seek healthcare. This study examines factors associated with depressive symptoms among non-Hispanic Black and Hispanic men ages ≥40 years with ≥1 chronic condition in the U. S.MethodsData from 1,907 non-Hispanic Black (n = 1,117) and Hispanic (n = 790) males with chronic conditions were analyzed using logistic regression to assess depressive symptoms, identified as a Patient Health Questionnaire-2 score ≥3. One model was fitted for all men, then separate models were fitted for non-Hispanic Black and Hispanic men, respectively. The models adjusted for sociodemographic, disease characteristics, health status, social engagement and support, and lifestyle behaviors.ResultsIn the full model, Hispanic men (OR = 1.39, p = 0.017) and those taking more medications (OR = 1.10, p = 0.010) were more likely to have depressive symptoms. Social disconnection (OR = 1.65, p < 0.001), reliance on others for health management (OR = 1.04, p < 0.001), limited activity due to health (OR = 3.15, p < 0.001), self-care barriers (OR = 1.16, p < 0.001), healthcare frustration (OR = 1.13, p < 0.001), prolonged sitting (OR = 1.01, p = 0.030), and tobacco use (OR = 1.56, p = 0.002) increased likelihood of depressive symptoms. Common and unique factors associated with depressive symptoms were identified in models for non-Hispanic Black and Hispanic men, respectively.ConclusionFindings highlight the dynamic interplay between depressive symptoms, social engagement, and lifestyle behaviors among non-Hispanic Black and Hispanic men with complex disease profiles. Efforts are needed to address depressive symptomatology through self-managing conditions, strengthening supportive networks, and alleviating burdens associated with healthcare interactions.